Convergência, participação e experiência midiática na publicidade: reconfigurações encontradas no festival Cannes Lions - Lima, Letícia Salem Herrmann (2015)
This doctoral dissertation aims to investigate the practices of the contemporary advertising, constructed from changes in the social dynamics that incorporate public participation in its conception, considering the creative processes that idealize hybrid formats in building their media. In an era of convergence, encouraging the involvement of the consumer in the communication processes caused structural changes in the traditional advertising, which was remodeled to fit more collaborative dynamics, offered openly to consumers, exploring entertainment resources that offer new experiences. It’s possible to observe the spreading of the advertising media from building consumer oriented exposure of their “identities”, mediated by the digital medium. The media circulation is intensified by the co-participation phenomena in which the consumer appropriates the original media, creating different content in order to integrate socially, increasing the visibility of their mediatic “self”, defined by the portrait of a digital “self”. This empirical study has analyzed the advertising categories of the “Cannes Lion International Festival of Creativity” of 11 years, in order to identify the changes in the creative design of the campaigns. An observation of the performance of the main awarded campaigns from 2013 and 2014 was made in terms of hybridization of cross-media and transmedia formats, co-creation, visibility, and circulation of media through appropriation or consumer participation in the contents. The theoretical basis of this study is supported by the cultural and media convergence (JENKINS, 2008) by the need to monitor the advertising momentum established by the daily practices. The main discussion of this study is the spreadable and spreadability of media (JENKINS, FORD, GREEN, 2013), the transmedia narrative, storytelling and the advertising hybridism (PHILLIPS, 2012), advertising ideologies and the sense schemes (FLOCH, 1993), the experience (QUÉRÉ, 2010; SCHMITT, 2002), and the construction of the “self” in the digital environment (TURKLE, 2011). As a result of this research I present indications of advertising activation via consumer “goal” stimulation, created by experiential stimuli ads, and via identification with the communicational proposal offered. Contemporary advertising proved to be made of empowering elements in its discourse, coming from formats that stimulate the retro-circulation and the spreadable media, the constructive participation, and public involvement in its spreadability, in which the central proposal is constituted of procedural dynamic of an “experiential advertising media”.